2019
DOI: 10.1164/rccm.201806-1109tr
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea, Hypoxia, and Nonalcoholic Fatty Liver Disease

Abstract: Recent studies have demonstrated that obstructive sleep apnea (OSA) is associated with the development and evolution of nonalcoholic fatty liver disease (NAFLD), independent of obesity or other shared risk factors. Like OSA, NAFLD is a prevalent disorder associated with major adverse health outcomes: Patients with NAFLD may develop cirrhosis, liver failure, and hepatocellular carcinoma. One major finding that has emerged from these studies is that the OSA-NAFLD association is related to the degree of nocturnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
139
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 113 publications
3
139
0
7
Order By: Relevance
“…Intermittent hypoxia can result in oxidative stress, IR, abnormal lipid metabolism, overactivation of the sympathetic nervous system, inflammation, and mitochondrial dysfunction, each of which plays important roles in development and progression of NAFLD. 92 Intermittent hypoxia activates hypoxia-inducible factors, which leads to increased synthesis of hepatic fat, upregulated hepatic inflammation, and fibrosis. The chronic intermittent hypoxia in morbidly obese subjects contributes to the severity of hepatic necroinflammation and fibrosis independent of adiposity.…”
Section: Pcosmentioning
confidence: 99%
“…Intermittent hypoxia can result in oxidative stress, IR, abnormal lipid metabolism, overactivation of the sympathetic nervous system, inflammation, and mitochondrial dysfunction, each of which plays important roles in development and progression of NAFLD. 92 Intermittent hypoxia activates hypoxia-inducible factors, which leads to increased synthesis of hepatic fat, upregulated hepatic inflammation, and fibrosis. The chronic intermittent hypoxia in morbidly obese subjects contributes to the severity of hepatic necroinflammation and fibrosis independent of adiposity.…”
Section: Pcosmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) represents a major global healthcare challenge in the twenty-first century. Driven by the obesity epidemic [1], the global prevalence of NAFLD is estimated at around 25.2%, and ranges from 13.5% in Africa to as high as 31.8% in the Middle East [2,3]. However, it is well established that there is significant variation in the presence of concurrent metabolic abnormalities such as hyperglycaemia, hypertension and hyperlipidaemia in patients with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been experimentally demonstrated that IH could be a major trigger for NAFLD. Indeed, IH directly induced hepatosteatosis through the administration of repetitive brief periods of hypoxia and reoxygenation mimicking OSA in animal models (28). Several studies from the same research group demonstrated that IH promoted hepatic lipid accumulation mainly by inducing de novo lipogenesis.…”
Section: Experimental Evidences Linking Intermittent Hypoxia To Nafldmentioning
confidence: 99%
“…OSA is especially prevalent among obese individuals, but IH may differently affect the liver and adipose tissue in obese patients as it has been strongly associated with liver damage, whereas, apparently, it has no effect on adipocyte morphology or adipose tissue macrophage accumulation (47). Several studies examining cohorts of obese patients with sleep apnea have found that IH is closely associated with NAFLD diagnosed using non-invasive tools (35), but, even more important, with the histological features of NASH including lobular inflammation, hepatic ballooning, and hepatic fibrosis (28). Interestingly, a dose-response relationship has been observed between the severity of nocturnal hypoxia and liver injury in obese patients in the absence of metabolic syndrome (38).…”
Section: Clinical Evidences Linking Osa To Nafldmentioning
confidence: 99%